2015
DOI: 10.1007/978-3-319-18365-7_7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of (−)-Epigallo-catechin-(3)-gallate on Amyloidogenic Proteins Suggests a Common Mechanism

Abstract: Studies on the interaction of the green tea polyphenol (−)-Epigallocatechin-3-gallate (EGCG) with fourteen disease-related amyloid polypeptides and prions Huntingtin, Amyloid-beta, alpha-Synuclein, islet amyloid polypeptide (IAPP), Sup35, NM25 and NM4, tau, MSP2, semen-derived enhancer of virus infection (SEVI), immunoglobulin light chains, beta-microglobulin, prion protein (PrP) and Insulin, have yielded a variety of experimental observations. Here, we analyze whether these observations could be explained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 107 publications
(273 reference statements)
3
60
0
Order By: Relevance
“…Compounds like EGCG can inhibit amyloid formation in a wide variety of misfolded proteins in vitro and in animal models (57). Preliminary evidence suggests that EGCG may counteract amyloid deposition in AL patients and improve their prognosis (34,35,58).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compounds like EGCG can inhibit amyloid formation in a wide variety of misfolded proteins in vitro and in animal models (57). Preliminary evidence suggests that EGCG may counteract amyloid deposition in AL patients and improve their prognosis (34,35,58).…”
Section: Discussionmentioning
confidence: 99%
“…When systematically reviewing EGCG mechanisms in various proteins, we found that EGCG binding to aggregation intermediates may inhibit amyloid formation very effectively in cases where these species are rate-limiting to amyloid formation (57). In other cases, amyloid formation is dominated by a structural transition or dissociation of the native protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] One of the frequently investigated amyloid inhibitors is epigallocatechin-gallate (EGCG; the major catechin present in green tea) ( Fig.S1B), a polyphenolic compound found in green tea extract. [8][9][10][11][12] EGCG has been shown to be an effective amyloid inhibitor for a variety of amyloid-forming peptides and proteins. In addition to small molecule modulation, metal ions were shown to play a role in amyloid aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40][41] Particularly interesting among these inhibitors are cyclic tetrapyrroles and related molecules (e.g., porphyrins, phthalocyanines, and corrins), which have been shown to modify the aggregation of multiple proteins exhibiting prion-like propagated misfolding, including Aβ, 42,43 tau, 44,45 and prion protein (PrP). [46][47][48][49][50][51] In some cases, these compounds are proposed to stabilize off-pathway oligomers, 52,53 whereas in others, they are proposed to stabilize monomers 54 or interfere with interactions stabilizing larger aggregates, 55 but in most cases, their mechanism of action is incompletely understood.…”
mentioning
confidence: 99%